Tasteful domesticity : women's rhetoric & the American cookbook 1790-1940 - Walden, Sarah (Pittsburgh series in composition, literacy, and culture., 2018)
"In Tasteful Domesticity, Sarah Walden demonstrates how women used the cookbook as a rhetorical space. Taste discourse engages cultural values as well a physical constraints, and thus serves as a bridge across the contested space of the self and the body, particularly for women in the nineteenth century. Cook-books represent important contact zones of social philosophies, cultural beliefs, and rhetorical traditions, and through their rhetoric, we witness women's varied roles."--Cover